Urinary Tract Infection (Homoeopathy for All, 2021)
defined as significant bacteriuria in the presence of a constellation of symptoms such as dysuria (painful urination), increased urinary frequency and urgency, suprapubic discomfort and costovertebral angle tenderness This includes a lower urinary tract infection cystitis (symptomatic infection of the bladder), or an upper urinary tract infection acute pyelonephritis (symptomatic infection of the kidney).  Urine typically doesn’t contain bacteria (germs). Urine is a by product of our filtration system the kidneys. When waste products and excess water is removed from the blood by the kidneys, urine is created. Normally, urine moves through the urinary system without any contamination. However, bacteria can get into the urinary system from outside of the body, causing problems like infection and inflammation. This is a urinary tract infection (UTI).
Keywords: kidneys; urine; urinary tract